2014
DOI: 10.4491/ksee.2014.36.8.579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Micro Organic Pollutants Removal Using Advanced Water Treatment Process and Nanofiltration Process

Abstract: Various kinds of micro organic pollutants have frequently been detected from a water system. Therefore, it is considered to be very important part in the drinking water treatment system. And the research about removal process and processing efficiency have been being conducted briskly. In this study, the removal efficiency was evaluated using advanced water treatment process and nanofiltration process. The removal efficiency of nanofiltration process was very different according to physical and chemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The species which had low removal rate overall removal rate for both ozonation method were bezafibrate, clarithromycin, ketoprofen, mefenamic acid and sulpiride, and except for sulpiride, kOW was hydrophobic higher than 2. This is consistent with the findings of the previous report [29], and is characteristic of the oxidation process that contrasts with the treatment pattern by membrane filtration. The hydrophobic and easily dissociated compound shows a high removal rate in membrane filtration, and the opposite properties are well treated in the oxidation process.…”
Section: Final Elimination Efficiency By Casesupporting
confidence: 93%
See 2 more Smart Citations
“…The species which had low removal rate overall removal rate for both ozonation method were bezafibrate, clarithromycin, ketoprofen, mefenamic acid and sulpiride, and except for sulpiride, kOW was hydrophobic higher than 2. This is consistent with the findings of the previous report [29], and is characteristic of the oxidation process that contrasts with the treatment pattern by membrane filtration. The hydrophobic and easily dissociated compound shows a high removal rate in membrane filtration, and the opposite properties are well treated in the oxidation process.…”
Section: Final Elimination Efficiency By Casesupporting
confidence: 93%
“…These showed a high removal rate (90.4%) through the microbubble process. Among them, ketoprofen had the lowest removal rate of 73.3% and 81.9%, respectively, for both processes, and in other papers has shown an 80% removal rate [29]. On the other hand, the UV process alone showed a removal rate of more than 90%, so it was confirmed that the ozone treatment process was relatively poor due to differences caused by the ozonation mechanism [30].…”
Section: Final Elimination Efficiency By Casementioning
confidence: 83%
See 1 more Smart Citation